We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
48
1
avatar+155 

help

 Oct 28, 2019
 #1
avatar+104933 
+1

The equation form we need is

 

(x + 9)^2              (y + 3)^2  

________   +      _________   =  1

    a^2                      b^2

 

 

a  = the length of the major axis / 2  =  14/2   = 7   ⇒  a^2  =  49   

c  = the distance from the center to the focii  = 3 ⇒  c^2  =  9

b^2  =   a^2  - c^2   =  49 - 9   = 40

 

So we have

 

(x+ 9)^2               (y + 3)^2

_______     +    _________  =     1

   49                       40

 

 

cool cool cool

 Oct 28, 2019

34 Online Users

avatar
avatar
avatar